Early Diagnosis and Differences in Progression of Fetal Encephalocele. (16th January 2020) - Ong, Alston G. J.; Rolnik, Daniel L.; Menezes, Melody; Meagher, Simon
Abstract : In this case series, we present 3 cases of very early prenatal diagnosis of encephalocele that, despite similar appearances at diagnosis, had different disease progressions. Two of the cases were carried to term, whereas 1 resulted in a termination of pregnancy. The diagnoses were made via ultrasound examinations before cell‐free DNA testing for chromosomal abnormality screening at 10 weeks' gestation, thereby highlighting the importance of performing a routine ultrasound examination before cell‐free DNA testing antenatally.